2018
DOI: 10.1002/2211-5463.12544
|View full text |Cite
|
Sign up to set email alerts
|

Nephronectin mediates p38 MAPK‐induced cell viability via its integrin‐binding enhancer motif

Abstract: Nephronectin ( NPNT ) is an extracellular matrix ( ECM ) protein involved in kidney development. We recently reported intracellular NPNT as a potential prognostic marker in breast cancer and that NPNT promotes metastasis in an integrin‐dependent manner. Here, we used reverse‐phase protein array ( RPPA ) to analyze NPNT ‐triggered intracellular signaling in the 66cl4 mouse br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…More recently, we reported the involvement of the NPNT integrin-binding motifs in enhancing BC lung metastasis in mice 19 . NPNT was also found to promote anchorage independent growth and survival, providing cancer cells with a growth benefit 19,34 . These results could indicate a functional role for NPNT in metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we reported the involvement of the NPNT integrin-binding motifs in enhancing BC lung metastasis in mice 19 . NPNT was also found to promote anchorage independent growth and survival, providing cancer cells with a growth benefit 19,34 . These results could indicate a functional role for NPNT in metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…[36]. More recently, it was reported that Npnt is a potential prognostic marker in breast cancer and that Npnt mediates p38 mitogen-activated protein kinase (MAPK)–induced cell viability [38]. Npnt expression was suppressed by fibroblast growth factor (FGF)-2 via c-Jun N-terminal kinase (JNK) in MAPK and Phosphoinositide 3-kinase (PI3K) pathways [39].…”
Section: Silicosis and Integrinmentioning
confidence: 99%
“…Of note, multiple independent studies have implicated nephronectin in the regulation of cellular proliferation. For instance, Steigedal et al (2018) have reported that nephronectin promotes proliferation of breast cancer cells by activating the p38-MAPK signaling pathway via its integrin-binding domain ( Toraskar et al, 2018 ). Arai et al (2017) propose that nephronectin regulates proliferation of dental epithelial stem cells by activating SOX2 expression via the EGF-like repeat domains.…”
Section: Discussionmentioning
confidence: 99%